A cross layer analysis of harq protocols in wireless networks - Burich, Mariano Eduardo (2017)
This work studies the potential improvements in terms of energy efficiency and throughput of a hybrid automatic retransmission request (HARQ) mechanism. The analysis includes both the physical (PHY) and medium access (MAC) layers. We investigate the trade-off provided by HARQ, which demands reduced transmit power for a given target outage probability at the cost of more accesses to the channel. Since the competition for channel access at the MAC layer is very expensive in terms of energy and delay, our results show that HARQ leads to great performance improvements due to the decrease in the number of contending nodes – a consequence of the reduced required transmit power. Counter-intuitively, our analysis leads to the conclusion that retransmissions may decrease the delay, improving the system performance. Finally, we investigate the optimum values for the number of allowed retransmissions in order to maximize either the throughput or the energy efficiency.